STRATEGIC PRIORITIES OF MEDICAL TOURISM DEVELOPMENT IN THE CONTEXT OF ECONOMIC DEVELOPMENTSTRATEGIC PRIORITIES OF MEDICAL TOURISM DEVELOPMENT IN THE CONTEXT OF ECONOMIC DEVELOPMENT - VAHANOVA, LIUDMYLA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to deepening the theoretical foundations of medical tourism development in Ukraine and substantiation of the multiplier effect of medical tourism. To this end, the four main motives of medical tourism in the world are considered (lower cost of treatment and diagnosis in another country; more modern medical technologies abroad; highly qualified medical care and service; time factor (with a long wait for medical treatment in their country)) main directions of medical tourism (inbound medical tourism and outbound medical tourism).It is established that at this stage of development of our country there is no regulatory regulation of medical tourism. There are only certain non-governmental organizations whose activities are aimed at: 1) development of medical tourism and involvement in the field of medical tourism of doctors interested in its development: Medical Tourism Association (UAMT) (established in 2013); 2) search for a clinic for a potential patient and provide such clinics with proposals to attract the best price experience and conditions to solve a problem (Medical Tourism Exchange, established in 2015).The reasons for the rapid development of the medical tourism industry in Ukraine are presented, the structure of outbound tourism in Ukraine by service providers is studied. Trends in the development of inbound medical tourism are analyzed.The analysis of the state of outbound and inbound medical tourism helped to generalize and highlight the main trends in the medical tourism market in Ukraine and the prerequisites for further development of its own segment of medical tourism, as well as to identify existing limitations and issues.Identification of existing restrictions in the development of medical tourism contributes to the search for tools to eliminate them and identify important areas of regional economic development of Ukrainian cities, based on the manifestation of the multiplier effect of medical tourism, in particular: communication services and information services; catering services; hotel services; leisure industry services and visits to cultural institutions; insurance services.
Keywords: medical tourism; inbound tourism; outbound tourism; cartoon effect